Current Updates on the Role of Microbiome in Endometriosis: A Narrative Review - Ser, Hooi Leng *; Au Yong, Siu Jung *; Mohamad Nasir, Shafiee; Norfilza, Mohd Mokhtar; Raja Affendi, Raja Ali * (MDPI, 2023)
Endometriosis affects approximately 6 to 10% of reproductive-age women globally. Despite much effort invested, the pathogenesis that promotes the development, as well as the progression of this chronic inflammatory disease, is poorly understood. The imbalance in the microbiome or dysbiosis has been implicated in a variety of human diseases, especially the gut microbiome. In the case of endometriosis, emerging evidence suggests that there may be urogenital-gastrointestinal crosstalk that leads to the development of endometriosis. Researchers may now exploit important information from microbiome studies to design endometriosis treatment strategies and disease biomarkers with the use of advanced molecular technologies and increased computational capacity. Future studies into the functional profile of the microbiome would greatly assist in the development of microbiome-based therapies to alleviate endometriosis symptoms and improve the quality of life of women suffering from endometriosis.